Dynamics of skimming flow in the wake of a vegetation patch - Mayaud, J; Wiggs, G; Bailey, R (Elsevier, 2016)
Dryland vegetation is often spatially patchy, and so affects wind flow in complex ways. Theoretical models and wind tunnel testing have shown that skimming flow develops above vegetation patches at high plant densities, resulting in little or no wind erosion in these zones. Understanding the dynamics of skimming flow is therefore important for predicting sediment transport and bedform development in dryland areas. However, no field-based data are available describing turbulent airflow dynamics in the wake of vegetation patches. In this study, turbulent wind flow was examined using high-frequency (10 Hz) sonic anemometry at four measurement heights (0.30 m, 0.55 m, 1.10 m and 1.65 m) along a transect in the lee of an extensive patch of shrubs (z = 1.10 m height) in Namibia. Spatial variations in mean wind velocity, horizontal Reynolds stresses and coherent turbulent structures were analysed. We found that wind velocity in the wake of the patch effectively recovered over ~12 patch heights (h) downwind, which is 2–5 h longer than previously reported recovery lengths for individual vegetation elements and two-dimensional wind fences. This longer recovery can be attributed to a lack of flow moving around the obstacle in the patch case. The step-change in roughness between the patch canopy and the bare surface in its wake resulted in an initial peak in resultant horizontal shear stress ( τr ) followed by significant decrease downwind. In contrast to τr , horizontal normal Reynolds stress (u'<sup2< sup=""> ) progressively increased along the patch wake. A separation of the upper shear layer at the leeside edge of the patch was observed, and a convergence of τr curves implies the formation of a constant stress layer by ~20 h downwind. The use of τr at multiple heights is found to be a useful tool for identifying flow equilibration in complex aerodynamic regimes. Quadrant analysis revealed elevated frequencies of Q2 (ejection) and Q4 (sweep) events in the immediate lee of the patch, which contributed to the observed high levels of shear stress. The increasing downwind contribution of Q1 (outward interaction) events, which coincides with greater u'<sup2< sup=""> and wind velocity, suggests that sediment transport potential increases with greater distance from the patch edge. Determining realistic, field-derived constraints on turbulent airflow dynamics in the wakes of vegetation patches is crucial for accurately parameterising sediment transport potential in larger- scale dryland landscape models. This will help to improve our understanding of how semi-vegetated desert surfaces might react to future environmental and anthropogenic stresses.</sup2<></sup2<>